Efektivitas Komunikasi Antarpribadi dalam Meningkatkan Kualitas Hubungan pada Bimbingan dan Penyuluhan Pendidikan Islam - Harahap, Hilda Rahmadani; Rokan, Muhammad Solihin; Alifah, Nisrina; Siregar, Suci Izmahani (LPPPI Publishing, 2025)
This research aims to examine the effectiveness of interpersonal communication in improving the quality of relationships in Islamic education guidance and counseling. Interpersonal communication, which involves direct, personal, and often reciprocal interactions, is an important mechanism for understanding students' needs, providing emotional support, and encouraging moral and spiritual growth. Using a descriptive approach and qualitative literature study methods, this research explores the principles of interpersonal communication, the dynamics of relationship development, and their application in the context of Islamic educational guidance. The research results show that effective interpersonal communication can increase mutual trust, understanding and cooperation between counselors and students. This creates a conducive learning environment and supports the holistic development of students in accordance with Islamic values. The conclusion of this research emphasizes the importance of effective communication as the basis for harmonious relationships in guidance and counseling in Islamic education. This research also provides practical insights for Islamic education counselors in optimizing their interactions to achieve better educational goals.